Rapid determination of peroxide value in crude palm oil products using Fourier transform infrared spectroscopy - Moh, M.H.; Tang, T.S.; Che Man, Y.B.; Lai, O.M. (Food & Nutrition Press, 1999)
A rapid Fourier transform infrared (FTIR) spectroscopic technique coupled with fixed NaCl cell (1 mm pathlength) was developed to measure peroxide value (PV) in crude palm oil (CPO) and crude palm kernel oil (CPKO). Calibration standards were prepared by oxidizing CPO in a fermentor at 60C over a period of 24 h. A partial least squares (PLS) calibration model for predicting PV was developed based on the 3710-3210 cm-1 spectral region with reference to a single-point baseline at 3710 cm-1. The optimization of calibration factors was guided by the predicted residual error sum of squares (PRESS) test. The standard deviation (SD) of the calibration obtained was 0.46 PV over the range of 0.51-17.82 PV and the correlation coefficient (R2) was 0.998. The model was validated with an independent set of samples consisting of both laboratory and field samples. The overall SD for the validation set was sligthly higher (SD = 1.46 PV) with R2 of 0.989. Thus, it was demonstrated that PV measured by FTIR techniques was comparable to that obtained by the chemical method. The FTIR method has the advantage of being rapid and requiring only a minimum amount of organic solvent.